2019
DOI: 10.17221/150/2018-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and accuracy of genomic prediction for production traits in Duroc pigs

Abstract: Genetic parameters and accuracy of genomic prediction for production traits in a Duroc population were estimated. Data were on 24 828 purebred Duroc pigs born in 2000–2016. After quality control procedures, 30 263 single nucleotide polymorphism markers and 560 animals remained that were used to predict the genomic breeding values of individuals. Accuracies of predicted breeding values for average daily gain (ADG), backfat thickness (BF), loin muscle area (LMA), lean percentage (LP) and age at 90 kg (D90) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
6
5
1
Order By: Relevance
“…According to Clutter [ 21 ], several studies reported an average h 2 of 0.49, which was in line with our findings. Lopez et al also had an h 2 of 0.35, further supporting our values [ 15 ]. In other studies, consistent h 2 estimates were published in Duroc pigs (0.53 ± 0.15) [ 33 ], as well as in Landrace (0.54 ± 0.01) and Yorkshire pigs (0.45 ± 0.01) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…According to Clutter [ 21 ], several studies reported an average h 2 of 0.49, which was in line with our findings. Lopez et al also had an h 2 of 0.35, further supporting our values [ 15 ]. In other studies, consistent h 2 estimates were published in Duroc pigs (0.53 ± 0.15) [ 33 ], as well as in Landrace (0.54 ± 0.01) and Yorkshire pigs (0.45 ± 0.01) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggested that ADG and DAYS105 were firmly and oppositely (−0.96 to −0.97) genetically linked. In Duroc pigs, a similar high, opposite correlation (−0.98) was reported previously [ 15 ]. Such high r g values essentially indicate that selection for either ADG or DAYS105 could result in favorable changes in both of these traits.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations